2019
DOI: 10.3389/fncel.2018.00532
|View full text |Cite
|
Sign up to set email alerts
|

High-Altitude Cognitive Impairment Is Prevented by Enriched Environment Including Exercise via VEGF Signaling

Abstract: Exposure to hypobaric hypoxia at high altitude (above 2500 m asl) causes cognitive impairment, mostly attributed to changes in brain perfusion and consequently neuronal death. Enriched environment and voluntary exercise has been shown to improve cognitive function, to enhance brain microvasculature and neurogenesis, and to be neuroprotective. Here we show that high-altitude exposure (3540 m asl) of Long Evans rats during early adulthood (P48–P59) increases brain microvasculature and neurogenesis but impairs sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 58 publications
0
24
0
Order By: Relevance
“…Angiogenesis is one of the key mechanisms of high-altitude adaptation [ 36 , 37 ]. Remarkably, FGF2 (fibroblast growth factor 2) ( di value = 10.53), one of the fibroblast growth factor family members ( FGFs) [ 38 ], has been proved as an angiogenic growth factor [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…Angiogenesis is one of the key mechanisms of high-altitude adaptation [ 36 , 37 ]. Remarkably, FGF2 (fibroblast growth factor 2) ( di value = 10.53), one of the fibroblast growth factor family members ( FGFs) [ 38 ], has been proved as an angiogenic growth factor [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…PE not only affects the activity of different brain cells, but also determines their survival and death. Recent evidence in a Long Evans rat model based study showed that voluntary exercise, in addition to enriched environment improves cognitive function, promoted neurogenesis and brain microvasculature in these rats exposed to hypobaric hypoxia at high altitudes by mediating VEGF signaling [ 111 ]. In a Wistar rat model, it was demonstrated that early PE in childhood and adolescence induces long term morphological alterations in hippocampal and cortical neurons even during the sedentary period of rats [ 112 ].…”
Section: The Role Of Exercise In Neurological Diseases and Involvementioning
confidence: 99%
“…Abnormal VEGF signaling caused by diabetes can lead to vascular dysfunction and pathological vessel remodeling, leading to vascular occlusion and insufficient blood supply[ 42 - 45 ]. Meanwhile, some studies found that the inhibition of VEGF signaling affected hippocampal dentate gyrus microvasculature and caused impairment in spatial memory[ 46 ]. Therefore, the decreased expression of VEGF in the late stage of diabetes led to hypoperfusion in the hippocampus, as found in the present study, leading to cognitive abnormalities.…”
Section: Discussionmentioning
confidence: 99%